2005
DOI: 10.1021/jm058043j
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II Receptor Ligands. From Agonist to Antagonist Activity

Abstract: Urotensin II (U-II) is a disulfide bridged peptide hormone recently identified as the ligand of a G-protein-coupled receptor. Human U-II (H-Glu-Thr-Pro-Asp-cyclo[Cys-Phe-Trp-Lys-Tyr-Cys]-Val-OH) has been described as the most potent vasoconstrictor compound identified to date. We have recently identified both a superagonist of hU-II termed P5U and the compound termed urantide, which is the most potent UT receptor peptide antagonist described to date. Our previous conformational studies showed that hU-II and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…Finally, replacement of the Tyr 9 residue in the P5U sequence with the benzothiazolyl-alanine or the (3,4-Cl)Phe moities leads to analogs with pEC 50 values at least 1.4 log higher than that of P5U being the most potent UT agonists discovered to date (Carotenuto et al, 2014 Fig. 10, compound 8) acts as a UT antagonist in the rat aorta bioassay (Patacchini et al, 2003;Camarda et al, 2004) but stimulates Ca 2+ mobilization in CHO cells transfected with human UT Grieco et al, 2005 ]UII (4)(5)(6)(7)(8)(9)(10)(11) ; Fig. 10, compound 9), which does not evoke any contraction of thoracic aorta rings, shifts to the right the UII concentration-response curve (Camarda et al, 2006).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, replacement of the Tyr 9 residue in the P5U sequence with the benzothiazolyl-alanine or the (3,4-Cl)Phe moities leads to analogs with pEC 50 values at least 1.4 log higher than that of P5U being the most potent UT agonists discovered to date (Carotenuto et al, 2014 Fig. 10, compound 8) acts as a UT antagonist in the rat aorta bioassay (Patacchini et al, 2003;Camarda et al, 2004) but stimulates Ca 2+ mobilization in CHO cells transfected with human UT Grieco et al, 2005 ]UII (4)(5)(6)(7)(8)(9)(10)(11) ; Fig. 10, compound 9), which does not evoke any contraction of thoracic aorta rings, shifts to the right the UII concentration-response curve (Camarda et al, 2006).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Structure-activity relationship studies (Flohr et al, 2002;Kinney et al, 2002;Brkovic et al, 2003;Labarrère et al, 2003;Chatenet et al, 2004;Guerrini et al, 2005;Leprince et al, 2008;Merlino et al, 2013) led to the discovery of peptide-derived analogs acting as potent agonists or antagonists (Behm et al, 2002;Grieco et al, 2002a;Herold et al, 2003;Patacchini et al, 2003;Carotenuto et al, 2004b;Grieco et al, 2005;Carotenuto et al, 2006;Chatenet et al, 2012Chatenet et al, , 2013a. However, those molecules are usually not considered as the best drug candidates, because their pharmacodynamic and pharmacokinetic properties (bioavailability, metabolic stability, biodistribution) are not optimal.…”
Section: Design Of Nonpeptidic Urotensin II Receptor Agonists and mentioning
confidence: 99%
“…Micelle solution was used, as we have reported the NMR structure of hU-II and other UT agonists [18,23,24] and antagonist [25,26] in this medium.…”
Section: Nmr Analysismentioning
confidence: 99%
“…For example, Urantide (10) shows a pA 2 = 8.3 in the rat isolated thoracic aorta assay [58]. The substitution of the Cys5 with penicillamine (β,β-dimethyl-cysteine, Pen), which enhances the agonist potency (hU-II(4-11)/P5U) [59], brings about only minor effects, if any, on partial agonists and antagonists [60]. Regoli et al recently reported that Urantide shows agonist activity in a calcium mobilization assay performed in CHO hUT cells [61].…”
Section: Peptide Ut Receptor Antagonistsmentioning
confidence: 99%
“…In contrast, in aqueous SDS micelle solution hU-II and some important analogues fold in a defined secondary structure [102]. In particular, in this environment we studied the endogenous ligand hU-II (1), the super-agonist [Pen5] U-II(4-11) (P5U) [102], the partial agonist/antagonist [Orn 8 ] U-II(4-11), the pure antagonist Urantide (10), and some inactive analogues [60]. The analyzed analogues which retain high affinity for UT receptor all possess a type II' β-hairpin backbone conformation encompassing residues 5-10 with a turn at position 7-8 regardless their agonist or antagonist activity, indicating that such backbone conformation is necessary for the UT receptor recognition.…”
Section: Nmr and Molecular Modeling Studiesmentioning
confidence: 99%